2019
DOI: 10.1111/jocd.12932
|View full text |Cite
|
Sign up to set email alerts
|

Review of sterility of reused stored dermal filler

Abstract: Objective: This review is primarily focusing on the legitimate concern about bacterial contamination after reuse of stored filling syringes and its associated risk of infections.Methods: A comprehensive literature review was done through searching the PubMed, Medline, Google Scholar, and ResearchGate without setting a time limit.The following search terms were used soft tissue filler, hyaluronic acid, or calcium hydroxylapatite AND sterility, safety, retouch, touch up, or reuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…In addition, the patient states that the stock of fillers at her provider’s office was investigated without any evidence of contamination. This finding is consistent with several reports about the sterility of partially used hyaluronic acid fillers [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the patient states that the stock of fillers at her provider’s office was investigated without any evidence of contamination. This finding is consistent with several reports about the sterility of partially used hyaluronic acid fillers [ 8 , 9 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our patient, the clinical assessment of the lumps as well as their subsequent pathologic examination (Figures 2 and 4) support the diagnosis of granulomatous formation. It seems that the initial injection of filler triggers a physiologic foreign body reaction as a result of an influx of inflammatory cells [5][6][7][8][9][10][11][12][13][14]16,18]. However, when there is a failure of effective phagocytosis of such inflammatory cells, the original self-limited response can progress to a severe inflammatory granulomatous process [10,13].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies and reviews found no evidence of contamination associated with reused HA gel fillers regardless of concentration and original injection site and no correlation between length of storage time and contamination risk. 1,2,[11][12][13] Storage in original syringes at room temperature in nonaseptic conditions for up to 12 months likely increases the risk. 11 Regarding direct evidence of contamination-related adverse effects in injected individuals, a somewhat dated retrospective review reported no infection in the only subject-based study that looked for adverse events among individuals injected with HA from stored filler syringes.…”
Section: Discussionmentioning
confidence: 99%
“…Hyaluronic acid (HA) is a widely accepted agent most commonly used as a dermal filler in facial aesthetic/cosmetic medicine. 1 2 Its main benefits include maintaining a youthful appearance, through facial rejuvenation and volume restoration secondary to aging or even post-traumatic facial disfiguration. 1 2 3 More recently, and as HA products continue to develop, attention has turned to the use of HA for body contouring and more specifically gluteal augmentation.…”
Section: Introductionmentioning
confidence: 99%
“… 1 2 Its main benefits include maintaining a youthful appearance, through facial rejuvenation and volume restoration secondary to aging or even post-traumatic facial disfiguration. 1 2 3 More recently, and as HA products continue to develop, attention has turned to the use of HA for body contouring and more specifically gluteal augmentation. 4 The common side effects of HA injection (HAI) are often minor and self-limiting.…”
Section: Introductionmentioning
confidence: 99%